Prevalence of Malnutrition and Its Risk Factors among Under-Five Children: A Case Study in the Second Congressional District of Camarines Norte, Philippines - Malabanan, Leni M.; Miguel, Eden C. (Journal of Public Health Sciences, 2025)
Malnutrition among children under five remains a critical public health concern, impacting growth, development, and overall well-being. This retrospective cohort study was conducted to thoroughly examine the prevalence of malnutrition and its associated risk factors among children under five in the Second Congressional District of Camarines Norte. Data collection involved reviewing documents, specifically the records of 340 under-five children obtained from the Field Health Service Information System (FHSIS). These records were assessed using a guide checklist, with the data analyzed through percentage technique, prevalence rates, odds ratios, and multivariate regression analysis. Results revealed a predominance of male children, most aged 24-35 months, with parents largely employed, high school graduates, and earning household incomes of Php 5,000–10,000 per month. Mild to moderate household food insecurity was also noted, necessitating attention to prevent long-term health impacts. Low household income strongly predicted underweight status, while stunting was significantly associated with low maternal education and maternal unemployment. However, none of these factors were significant predictors of wasting. Furthermore, no significant correlation was found between malnutrition indicators (underweight, stunting, wasting) and healthcare service utilization, including routine check-ups, growth monitoring, and nutrition counseling. The study underscores the importance of targeted nutritional interventions addressing stunting and iron deficiency, coupled with strategies to improve maternal education and employment. A proposed plan has been developed to enhance the nutritional status of under-five children and reduce malnutrition prevalence through comprehensive, community-focused approaches.